Problems of development of the carbon market of Kazakhstan (Eurasian Journal of Ecology, 2016)
Discusses the legislative and organizational problems faced in the creation of the carbon market. Some suggested solutions.
Keywords: Verification of enterprises; quotas; carbon credits; greenhouse gases; the national allocation plan; economic diversification